Research supervision: Perceptions of postgraduate nursing students at a higher education institution in KwaZuluNatal South Africa - S Mthembu; C Muraraneza; F Mtshali (South African Medical Association, 2016)
Background. Scientific advancement, particularly in the area of information communication technology (ICT), challenges the mode of knowledgeadvancement at universities. Such challenges are especially evident in the area of postgraduate (PG) research supervision, particularly in the light ofÂ the changing studentsâ€™ demography, whereby there is a radical shift from full-time campus-based students to part-time students. This challenge isÂ compounded by many countries not considering research competency as a requirement for PG supervision â€" the result of static and outdated curricula.Objective. To explore the perceptions of PG nursing students with regard to the research supervision process.Methods. A quantitative research study was conducted at the University of KwaZulu-Natal (UKZN), Durban, South Africa using non-convenience sampling.The PG Research Experience Survey questionnaire was adapted for the current study. Ethical clearance was obtained from UKZNâ€™s Ethics Committee.The population consisted of the PG coursework Masterâ€™s nursing students who were registered for the research project module during 2012. A total of 56students participated, with a response rate of 70%. Data were analysed using the Statistical Package for the Social Sciences 19 (SPSS 19) (IBM Corp., USA).Results. The findings revealed that more than half of the respondents (66.2%; n=37) rated the level of support from research supervisors as moderateon a scale of low to high. The period of research supervision, mode of attendance and status within the university were identified as factors influencingthe perceptions of support from research supervisors.Conclusion. This study recommends that, to improve the quality of research supervision, there is a need to include a research supervision module inthe curriculum of nurse educators and to adopt online research supervision, underpinned by the extensive use of ICT to accommodate both part-timeand full-time PG students.